Synthesis of MnO2 Particles via One Step Localized Heating Method as Catalyst for Dye Degradation - Pung Swee Yong (Malaysian Catalysis-An International Journal, 2022)
This work demonstrated the synthesis of MnO2 particles via a rapid one-step localized heating method. The heat was transferred directly from the wire into the precursor solution, hence minimized the heat loss to the surrounding. As a result, the precursor solution was heated up rapidly and MnO2 particles with different morphologies were successfully synthesized in short duration within 10 to 15 min. These MnO2 particles were used as catalyst in the degradation of Rhodamine B (RhB) organic dye. Particularly, MnO2 particles synthesized at 10 min possessed outstanding catalytic activity with 99% degradation efficiency of RhB dye in 10 min of reaction time. This was greatly contributed by its 3D nanoflowers morphology that provided more active sites for catalytic activities to occur. The promising catalytic activity, synthesizing by a simple and affordable synthesis setup could provide an alternative in the development of MnO2 catalyst for organic pollutants removal.